Criação e compartilhamento de informação e conhecimento em aglomerações produtivas: o APL de móveis de Ubá - MG - Wilson Jose Vieira da Costa (2007)
The objective of this investigative work is to identify the process of creation and sharing knowledge in a local productive cluster and the influence of the institutional support in this process of collective learning and innovation. A case study was done as research methodology in the local inter-organizational network of furniture industry in Ubá-MG with qualitative and quantitative approaches. The results show that the measuring between MPME and the current competitive environment is made easy by the network formate, before an institutional support within the companies and the interaction among them (ba). This evidence shows that the MPME, in isolation, cannot complete the spiral of knowledge creation, but when organized in the interorganizational networks not only complete that cycle but, also expand it by the interactions among collective actions of development.